ANALISIS SISTEM PENERAPAN E-LEARNING DENGAN MENGGUNAKAN METODE UTAUT (UNIFIED THEORY OF ACCEPTANCED USE OF TECHNOLOG) (Study Kasus : STMIK XYZ) - Ery Hartati (Jurnal Informatika Global)
Online Learning System is a Web-based Learning Management System (LMS) developed by STMIK XYZ to improve the effectiveness and qualityLearning. Online Media has a number of facilities such as online assignments, lecture materials, chating, answering questionnaires, viewing announcements, course forums, activity calendars and so on. This paper describes the results of research on the relationship of factors that affect the acceptance and use of E-learnig by using Unified Theory of Acceptance and Use of Technology (UTAUT). Data collected from respondents (students) and teachers who use Online Media through data collection from the database and the distribution of questionnaires of 100 respondents. The result of descriptive analysis shows that most of the respondents have a high level of performance expectancy, effort expectancy, social influence, facilitating conditions, and use behavior, while the behavioral intention rate is mostly moderate. The result of multiple regression test showed a very strong relationship between vairable performance expectancy, effort expectancy, each having positive and significant result (p-value <0,00) to behavioral intention.Keywords : Learning Management System, e-Learning, UTAUT